Prognosis Associated With CA19-9 Response Dynamics and Normalization During Neoadjuvant Therapy in Resected Pancreatic Adenocarcinoma. Issue 3 (26th March 2023) - Newhook, Timothy E.; Vreeland, Timothy J.; Griffin, James F.; Tidwell, Rebecca S. S.; Prakash, Laura R.; Koay, Eugene J.; Ludmir, Ethan B.; Smaglo, Brandon G.; Pant, Shubham; Overman, Michael; Wolff, Robert A.; Ikoma, Naruhiko; et al.
Abstract : Objective: To characterize associations between carbohydrate antigen 19–9 (CA19–9) dynamics during neoadjuvant therapy (NT) and survival for patients with pancreatic ductal adenocarcinoma (PDAC). Background: Although normalization of CA19–9 during NT is associated with improved outcomes following PDAC resection, we hypothesize that CA19–9 dynamics during NT can improve prognostication. Methods: Characteristics for patients with PDAC undergoing NT (July 2011–October 2018) with ≥3 CA19–9 results (bilirubin<2mg/dL) were collected and grouped by CA19–9 dynamics. Nonproducers (<1 U/ml) were excluded, and normal was ≤35 U/ml. Postresection survival was compared among groups. Results: Of 431 patients, 166 had eligible CA19–9 values. Median baseline CA19–9 was 98 U/ml. Overall 2-year postresection recurrence-free survival (RFS) and overall survival (OS) were 37% and 63%, respectively. Patients with normalization (53%) had improved 2-year RFS (47% vs. 28%, P = 0.01) and OS (75% vs. 49%, P = 0.01). CA19–9 dynamics during NT were analyzed by shape, direction, and normalization creating response types ("A-B-C-D-E"). Type A was "Always" decreasing to normalization, B "Bidirectional" with eventual normalization, C "Consistently" normal, D any "Decrease" without normalization, and E "Elevating" without normalization. Types A and B responses were associated with the longest postresection 2-year RFS (51% and 56%) and OS (75% and 92%, respectively) whereas Types D and E had the worst outcomes. After adjusting for node-positivity, perineural invasion, and margin-positivity, CA19–9 response types were independently associated with both RFS and OS, and predicted outcomes are better than CA19–9 normalization alone (likelihood ratio test RFS P < 0.001, OS P = 0.01). Conclusions: This novel A-B-C-D-E classification of CA19–9 dynamics during NT was associated with postresection outcomes more precisely than CA19–9 normalization alone.